Detecting Sunyaev-Zel'dovich clusters with PLANCK: II. foreground components and optimised filtering schemes - Schäfer, Björn Malte; Bartelmann, Matthias (Arxiv, 2008)
The PLANCK mission is the most sensitive all-sky CMB experiment currently planned. The High Frequency Instrument (HFI) will be especially suited for observing clusters of galaxies by their thermal Sunyaev-Zel'dovich (SZ) effect. In order to assess PLANCKs SZ-capabilities in the presence of spurious signals, a simulation is presented that combines maps of the thermal and kinetic SZ-effects with a realisation of the cosmic microwave background (CMB), in addition to Galactic foregrounds (synchrotron emission, free-free emission, thermal emission from dust, CO-line radiation) as well as the sub-millimetric emission from celestial bodies of our Solar system. Additionally, observational issues such as the finite angular resolution and spatially non-uniform instrumental noise of PLANCKs sky maps are taken into account, yielding a set of all-sky flux maps, the auto-correlation and cross-correlation properties of which are examined in detail. In the second part of the paper, filtering schemes based on scale-adaptive and matched filtering are extended to spherical data sets, that enable the amplification of the weak SZ-signal in the presence of all contaminations stated above. The theory of scale-adaptive and matched filtering in the framework of spherical maps is developed, the resulting filter kernel shapes are discussed and their functionality is verified.
Gesehen am 25.09.2017